A prospective observational study on drug safety monitoring and Pharmacoeconomics in patients with locally advanced unresectable NSCLC in a tertiary care hospital - Sreenivasan, Jayakumar; Mohamedali, Seema P. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Lung cancer is the deadliest type of cancer for both men and women. The study was aimed at learning and comparing the toxicities of various chemotherapeutic regimens for the treatment of carcinoma lung, which will help in the implementation of counter measures to avoid development of toxicities, with a constant vigil on the patients during chemotherapeutic cycles. This study also aimed at searching into the added economic burden to the unfortunate patient, who is already suffering from a deadly disease. Study also targeted at evaluating the performance status of the patients receiving the chemotherapy. Methods: The Adverse Drug Reactions (ADR) data was collected from 40 patients receiving chemotherapy for locally advanced unresectable carcinoma lung from the cancer wards of a tertiary care hospital over a period of 2 months. ADRs were graded according to WHO guidelines and their performance statuses were assessed using the Zubrod’s performance scale. Cost analysis of chemotherapeutic regimens was also carried out. Results: On comparison, alopecia and peripheral neuropathy were significantly more common with carboplatin-paclitaxel combination compared to other regimens (p value<0.005). Cost analysis reveals that the most commonly employed carboplatin-paclitaxel combination is more affordable when compared to the newer highly expensive agents but is costlier than cisplatin based chemotherapy. Also, carboplatin-paclitaxel combination offers a reasonably good performance status. Conclusions: Thus, carboplatin-paclitaxel combination is the preferred regimen for palliation in advanced NSCLC, especially in the older patients.